Analisis Faktor-faktor Penentu Keberhasilan Inseminasi Buatan (Ib) Ternak Sapi Potong di Kabupaten Tanjung Jabung Barat - Setiawan Setiawan; Fachroerrozi Hoesni; Bagus Pramusintho; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the dominant factors, both direct and indirect, to the success rate of the IB program in West Tanjung Jabung Regency. This research was carried out from 12 December 2020 to 6 January 2021. The objects observed in this study were all inseminators and a sample of breeders from each inseminator. The data obtained from this study are primary data and secondary data. The data were analyzed using Stepwise Multiple Regression analysis and processed using SPSS. The results of the analysis show that the success of Artificial Insemination in West Tanjung Jabung Regency has been good, this can be seen from the S/C value per inseminator of 1.54 Â± 0.46. The dominant factors directly and indirectly influence the success of AI in West Tanjung Jabung Regency such as the length of time of raising livestock, the skill factor of the inseminator, the work area factor, the age factor of the acceptor. Based on this research, it can be concluded that the success of the Insemination program (Artificial AI) in West Tanjung Jabung Regency is quite good. This can be seen from the Service Perception (S/C) value in Tanjung Jabung Barat Regency, which is 1.54 Â± 0.63, which shows the fertility level of acceptor cattle is quite good, the dominant factors that influence the success of AI in West Tanjung Jabung Regency are length of breeding, inseminator factors, area factors and acceptor age factors, while the farmer's knowledge factor and BCS factor do not significantly affect the success of AI in Tanjung Regency. West Jabung, the BCS factor does not have a significant effect because livestock from the study in the West Tanjung Jabung Regency area have a homogeneous BCS score.